PENGARUH GROWTH OPPORTUNITY, LIQUIDITY, TANGIBILITY, DAN FIRM SIZE TERHADAP CAPITAL STRUCTURE - Venni Julyandy Putri; Ardiansyah Ardiansyah (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This study aims to obtain empirical evidence regarding the effect of growth opportunity, liquidity, tangibility, and firm size on the capital structure of manufacturing companies in the consumer goods industries and miscellaneous industries listed on the IDX in 2018-2020. Sample selection using purposive sampling method with the valid data as many as132 samples consisting of 44 companies. The data processing technique used multiple regression analysis assited by the Eviews version 12 program and Microsoft Excel 2007. The results showed that growth opportunity, liquidity, and tangibility had no significant effect on capital structure, while firm size shows that there is an effect positive and significant to the capital structure.